2015
DOI: 10.1080/15548627.2015.1063871
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive detection of lysosomal membrane permeabilization by lysosomal galectin puncta assay

Abstract: Lysosomal membrane permeabilization (LMP) contributes to tissue involution, degenerative diseases, and cancer therapy. Its investigation has, however, been hindered by the lack of sensitive methods. Here, we characterize and validate the detection of galectin puncta at leaky lysosomes as a highly sensitive and easily manageable assay for LMP. LGALS1/galectin-1 and LGALS3/galectin-3 are best suited for this purpose due to their widespread expression, rapid translocation to leaky lysosomes and availability of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
332
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(363 citation statements)
references
References 58 publications
27
332
2
2
Order By: Relevance
“…Immediately upon blue-light illumination (GFP filter set, 3.9 W/ cm 2 , 5 min), the appearance of a number of mDsRed-Galectin1 red fluorescent puncta was observed (Supplementary Figure S3). Although these puncta were not as numerous as in the case of chemically-induced LMP (17), we concluded that at least some lysosomes underwent LMP in our experiments.…”
contrasting
confidence: 51%
See 1 more Smart Citation
“…Immediately upon blue-light illumination (GFP filter set, 3.9 W/ cm 2 , 5 min), the appearance of a number of mDsRed-Galectin1 red fluorescent puncta was observed (Supplementary Figure S3). Although these puncta were not as numerous as in the case of chemically-induced LMP (17), we concluded that at least some lysosomes underwent LMP in our experiments.…”
contrasting
confidence: 51%
“…To test this hypothesis, we used an elegant method for LMP detection that was recently described (17). This assay is based on the translocation of fluorescently labeled cytoplasmic galectins (e.g., galectin 1 or 3) into leaky lysosomes that results in clearly visible punctate patterns in the cells.…”
mentioning
confidence: 99%
“…Furthermore, the difference in DNA damage induced by unmethylated DQs versus the corresponding methylated analogs increased with increasing linker length for each pair of compounds. The integrity of the lysosomal membrane was interrogated by detection of lectin galactoside binding soluble 3 (LGALS3)/galectin-3 localization, which was recently demonstrated to rapidly translocate to damaged lysosomes (21). When lysosomes are healthy, galectin-3 is uniformly dispersed throughout the cell.…”
Section: Resultsmentioning
confidence: 99%
“…The lysosomotropic compound LLOME (L-leucyl-L-leucine O -methyl ester) is commonly used to rupture endolysosomes (3, 23, 24). LLOME rapidly permeates cellular membranes and accumulates in the lumen of acidified organelles, where it is condensed into a membranolytic polymer by the lysosomal enzyme cathepsin C (9, 23).…”
Section: Escrts Respond To Endolysosomal Damagementioning
confidence: 99%